The investment opportunity set and corporate ownership, directorship, auditing, and disclosure policies : some New Zealand evidence : a thesis submitted in partial fulfilment of the requirements for the degree of Doctor of Philosophy in the Department of Accountancy and Business Law, College of Business, Massey University - Hossain, Mahmud; Hossain, Mahmud (Massey University, 1998)
Recent studies in accounting and finance indicate that accounting and other important corporate policy decisions (e.g., debt, dividend, compensation, disclosure, and hedging) are related to investment opportunities present in the firm. My study attempts to augment this research by investigating whether decisions about the level of managerial share ownership, percentage of outside directors, quality of audit services, and amount of forward-looking information disclosure are also related to the investment (growth) opportunities. I argue that because the incentive problem between the manager and shareholders is an increasing function of the firm's IOS (a combination of growth options and specific assets-in-place), firms with more growth options will be motivated to use various mechanisms including managerial share ownership, outside directors, high quality audit services, and prospective information disclosure to mitigate agency problems. Using data from 80 New Zealand (NZ) companies listed on the stock exchange in 1995, the cross-sectional tests reveal that the IOS is positively and significantly related to managerial share ownership, outside directors, auditing, and disclosure polices. Because the monitoring mechanisms employed at a particular point in time could be driven by past growth or changes in past growth and because firms select a mix of mechanisms to align manager-shareholder interests, I also use time series-tests for the period 1991-1995 to determine whether changes in the mix of these mechanisms are related to the changes in IOS. The results indicate that changes in the pairwise mix between outside directors and auditing, outside directors and disclosure, and inside ownership and disclosure are not significantly related to changes in IOS. By contrast, predictions about the changes in the pairwise mix between disclosure and auditing, inside ownership and outside directors, and inside ownership and auditing and changes in IOS are supported. Thus, the time-series tests provide limited support for the predictions that the pairwise mix between monitoring mechanisms will change with IOS. Nevertheless, the results of this study provide useful insights into ownership concentration, board composition, auditing, and disclosure practices in NZ and add to the growing literature on investment opportunities.
Keywords: Disclosure (Accounting); Corporate governance